2010
DOI: 10.1037/a0017636
|View full text |Cite
|
Sign up to set email alerts
|

“Walking over 'em”: An exploration of relations between emotion dysregulation, masculine norms, and intimate partner abuse in a clinical sample of men.

Abstract: This study is the first to examine relations of emotion dysregulation, masculine norms, and abuse perpetration among men referred for domestic assault. Experiences of 108 men participating in batter intervention programs from 3 different cities were examined. Results suggest that intimate partner abuse, emotion dysregulation, and the specific masculine norms of dominance, emotional control, and self-reliance are associated. Multiple-regression analysis indicated that emotion dysregulation and the masculine nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 35 publications
5
64
1
1
Order By: Relevance
“…Participants' mean score on the PCL-C was 36.46 (SD = 11.45), which is slightly below commonly used cutoffs indicating possible PTSD diagnosis among civilians (McDonald & Calhoun, 2010), as well as scores among individuals seeking substance use treatment (Tull, Gratz, Aklin, & Lejuez, 2010). Emotion dysregulation subscales scores on the DERS were similar to or slightly higher than those reported among undergraduate student samples (Cohn, Jakupcak, Seibert, Hildebrandt, & Zeichner, 2010;Gratz & Roemer, 2004) and similar to or slightly lower than those reported among clinical samples (Ehring & Quack, 2010;Tager et al, 2010). Approximately 17% (n = 10) of participants reported perpetrating aggression in the three months prior to assessment, and the sample endorsed approximately 1.5 (SD = 6.74) acts of aggression during this time period.…”
Section: Data Analysis Plansupporting
confidence: 61%
“…Participants' mean score on the PCL-C was 36.46 (SD = 11.45), which is slightly below commonly used cutoffs indicating possible PTSD diagnosis among civilians (McDonald & Calhoun, 2010), as well as scores among individuals seeking substance use treatment (Tull, Gratz, Aklin, & Lejuez, 2010). Emotion dysregulation subscales scores on the DERS were similar to or slightly higher than those reported among undergraduate student samples (Cohn, Jakupcak, Seibert, Hildebrandt, & Zeichner, 2010;Gratz & Roemer, 2004) and similar to or slightly lower than those reported among clinical samples (Ehring & Quack, 2010;Tager et al, 2010). Approximately 17% (n = 10) of participants reported perpetrating aggression in the three months prior to assessment, and the sample endorsed approximately 1.5 (SD = 6.74) acts of aggression during this time period.…”
Section: Data Analysis Plansupporting
confidence: 61%
“…Previous research indicates that emotional dysregulation is a significant predictor of both physical and psychological IPV perpetration in a clinical sample (Tager et al, 2010), so it was somewhat unexpected that emotional dysregulation was consistently not significant in the initial multiple regression analyses and less predictive of IPV in the dominance analyses. Emotional dysregulation has not been examined in a sample of men seeking treatment for alcohol-use disorders, so the finding may suggest that different processes are in place for IPV perpetrated by a clinical, compared to a substance abusing, sample.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Gratz and Roemer (2004) found that emotional dysregulation was associated with male physical and sexual IPV perpetration among undergraduates. Similarly, Tager, Good, and Brammer (2010) examined emotion regulation and masculine norms among a clinical sample of men referred for engaging in IPV and found that emotional dysregulation, which accounted for 18% of unique variance, was the strongest predictor of perpetration of physical and psychological IPV. Moreover, emotional dysregulation in the context of alcohol abuse could work synergistically to increase chances for IPV perpetration.…”
mentioning
confidence: 99%
“…Emotion regulation difficulties are reported to be common in individuals with depression and anxiety disorders (Tull et al, 2007) and increased emotion regulation difficulties are related to IPV perpetration Shorey et al, 2011;Tager et al, 2011).…”
Section: Discussionmentioning
confidence: 99%